2019
DOI: 10.18332/tpc/112249
|View full text |Cite
|
Sign up to set email alerts
|

Male students’ experiences on predictors of waterpipe smoking reduction: A qualitative study in Iran

Abstract: INTRODUCTION In recent years, waterpipe smoking (WPS) has increased among adolescents in Iran. This study aimed to explain the experiences of high school students in Iran on predictors of WPS reduction based on a multi-theory model (MTM) of health behaviour change. METHODS This study was a qualitative study of directed content analysis that was conducted in high school male students in Hamadan, Iran, in 2017. In this study, 34 students who had smoked waterpipe (WP) in the last month were recruited through snow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…In terms of the predictors of WPS, Bashirian et al demonstrated that the belief in an individual's ability, support from friends, and the benefits of reducing waterpipe smoking are the most important factors in reducing WPS among students [18]. This supports our observation that friends have a significant impact in whether one will start or quit smoking.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of the predictors of WPS, Bashirian et al demonstrated that the belief in an individual's ability, support from friends, and the benefits of reducing waterpipe smoking are the most important factors in reducing WPS among students [18]. This supports our observation that friends have a significant impact in whether one will start or quit smoking.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have been conducted on smoking behavior based on the MTM theory including smoking cessation, tobacco cessation, water pipe smoking, cigarette smoking, substance use behavior, [14, 17, 18,19,20,35, 36, 37]. The initiation and sustenance of behavior change are substantiated in predicting health behavior changes by the finding of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to identify the correlates of sunscreen use, based on the fourth-generation multi-theory model (MTM) of health behavior change among Florida residents. MTM has been tested or applied to explain various health behaviors in community settings [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The results of the study were encouraging; the contribution of MTM constructs in all four models tested were significant and accounted for a substantial proportion of variance in the dependent variables.…”
Section: Discussionmentioning
confidence: 99%